2018
DOI: 10.3389/fendo.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Walking Training Causes a Decrease in Blood Cholesterol in Elderly Women Supplemented with Vitamin D

Abstract: ObjectiveDifferent studies have demonstrated that regular exercise can induce changes in the lipid profile, but results remain inconclusive. Available data suggest that correction of vitamin D deficiency can improve the lipid profile. In this study, we have hypothesized that Nordic Walking training will improve lipid profile in elderly women supplemented with vitamin D.MethodsA total of 109 elderly women (68 ± 5.12 years old) took part in the study. First group [experimental group (EG): 35 women] underwent 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
4
22
0
1
Order By: Relevance
“…We have previously shown that NW training leads to some adaptive changes in elderly women, as manifested by increased physical performance, decreased blood cholesterol levels, and reduced body iron stores. 19,25,26 In the present study, we confirmed that NW induces a reduction in serum ferritin levels, which is a good marker of body iron stores in the absence of inflammation. 27 Detailed analysis of the general significant decrease of serum ferritin levels indicated that some subjects did not respond to the training, albeit the reason for this was not known.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We have previously shown that NW training leads to some adaptive changes in elderly women, as manifested by increased physical performance, decreased blood cholesterol levels, and reduced body iron stores. 19,25,26 In the present study, we confirmed that NW induces a reduction in serum ferritin levels, which is a good marker of body iron stores in the absence of inflammation. 27 Detailed analysis of the general significant decrease of serum ferritin levels indicated that some subjects did not respond to the training, albeit the reason for this was not known.…”
Section: Discussionsupporting
confidence: 84%
“…These observations were in agreement with earlier studies. 24,25 After 12 weeks of training, a significant improvement in the physical fitness of subjects was noted (Table 2). The strength of the leg (p=0.00) and arm muscles (p=0.02) was improved.…”
Section: Effectiveness Of the Training On Functional Levelmentioning
confidence: 99%
“…The study investigated the impact of the 12-week NW training programme with additional supplementation of Vitamin D in elderly women. Previous studies have shown that this kind of training combined with Vitamin D supplementation can provide beneficial effects in terms of total cholesterol, triglycerides, low-density lipoprotein cholesterol [ 36 ], pro-inflammatory markers [ 15 ] and cognitive functions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the start of the experiment, the participants attended a meeting covering the training procedure and dietary recommendations. The training schedule was based on a published program [21,22].…”
Section: Exercise Protocol and Dietmentioning
confidence: 99%